LOGÍSTICA DE EMBARCAÇÕES PARA CONEXÃO DE POÇOS DO PRÉ-SAL - Gomes, Carlos Francisco Simões; Bianco, Bruno Pereira; Chaves, Maria Cecilia Carvalho (Pesquisa Operacional para o Desenvolvimento, 2015)
XX